Mechanical Characterization of Pre-Fatigued Free-Cutting Steels under Dynamic Tension - ITABASHI, Masaaki; KOSEKI, Heikichi (Engineering Transactions, 2014)
In the near future, toxic Pb will be prohibited to add to free-cutting steels. So far, many types of free-cutting steels without Pb have appeared. In order to compare dynamic mechanical properties of Pb added SUM24L steel (refer to JIS G 4804:2008, equivalent to AISI 12L14 steel) with those for Pb free SUM23 (equivalent to AISI 1215), high velocity tensile tests are carried out at a strain rate of 1×103 s−1, at room temperature. A half of the specimens are pre-fatigued before the dynamic tensile test. This loading combination, fatigue and impact, simulates a certain service condition, normal operational loadings and an accidental dynamic loading. Tensile strength of the pre-fatigued specimens is less than that of the virgin specimens, to some extent, for both steels. Where the degradation is of almost the same level, replacement of the Pb added free-cutting steel with the Pb free steel may be possible.